Pengaruh Pengalaman Kerja, Budaya Organisasi, Dan Lingkungan Kerja Terhadap Kinerja Pegawai - Waroi, Jubelina; Irawan, Andri; Mustajab, Duta (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study is an associative research study that explores the relationship between work experience, organizational culture, and work environment influence on employee performance at the Secretariat of the Regional People's Representative Council (DPRD) of Papua Province. The population in this study consists of employees in the Secretariat of the DPRD of Papua Province, a total of 91 respondents. Using the total sampling technique or saturation sampling, the sample data used in the study amounted to 87 respondents. This research's primary data source is questionnaires distributed to all respondents. The statistical method used to test the hypothesis is multiple linear regression analysis with the assistance of SPSS. Based on the results of the partial and simultaneous tests, the variables of Work Experience, Organizational Culture, and Work Environment have a positive and significant effect on the performance of employees at the Secretariat of the DPRD of Papua Province. This study highlights the dynamics within the Secretariat of the DPRD of Papua Province and provides a deeper understanding of the factors influencing employee performance.